2009
DOI: 10.1177/000348940911800812
|View full text |Cite
|
Sign up to set email alerts
|

Typing Vocal Fold Vibratory Patterns in Excised Larynx Experiments Via Digital Kymography

Abstract: Imaging with DKG demonstrated an ability to assign a signal type to various laryngeal vibrations. Signal typing techniques utilizing direct observation of the vocal folds could be useful in determining valid methods for the analysis of vocal fold vibrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…4). Restoration of a normal mucosal wave, indicated by symmetric and periodic sinusoidal functions with sustained inter‐vocal fold contact between cycles,44 also occurred in some larynges after AA (Fig. 6).…”
Section: Discussionmentioning
confidence: 87%
“…4). Restoration of a normal mucosal wave, indicated by symmetric and periodic sinusoidal functions with sustained inter‐vocal fold contact between cycles,44 also occurred in some larynges after AA (Fig. 6).…”
Section: Discussionmentioning
confidence: 87%
“…[80] identified three different vocal fold vibratory patterns in excised canine larynges using digital kymography (DKG). The type 1 pattern showed a periodic time-series of glottal edges and a distinct frequency spectrum.…”
Section: Excised Human and Animal Larynx Experimentsmentioning
confidence: 99%
“…It can be used for tasks involving vocal attack, coughing, throat clearing, laughing, and other activities involving rapid laryngeal maneuvers. In a recent study [16*], imaging with DKG demonstrated an ability to assign a signal type to various laryngeal vibrations. Braunschweig et al [17*] used HSV to develop a quantitative parameterization scheme of the phonatory onset, a new approach in developing objective methods for the diagnosis of functional dysphonia.…”
Section: High-speed Videoendoscopymentioning
confidence: 99%